The Association Between Cyberbullying Victimization and Suicidal Ideation Among Chinese College Students: The Parallel Mediating Roles of Core Self-Evaluation and Depression - Chu, Xiaowei; Yang, Sumin; Sun, Zhaoxing; Jiang, Min; Xie, Ruibo (Frontiers in Psychiatry, 2022)
With the rapid development of science and technology, the Internet has formed a new form of aggression, which is called cyberbullying. Many studies have demonstrated that cyberbullying can cause serious damage to the physical and mental health of Chinese college students, such as leading to depression and suicide. The main purpose of this study was to investigate the relationship between cyberbullying victimization and suicidal ideation and the parallel mediating roles of core self-evaluation and depression. A questionnaire was used to measure the research variables in this study among 1509 college students. The results indicated that: After controlling for participants’ gender, age, family structure, and family economic status, cyberbullying victimization significantly and positively related to suicidal ideation. Core self-evaluation and depression separately mediated the relationship between cyberbullying victimization and suicidal ideation. The mediating effect of depression was stronger than that of core self-evaluation.The findings support a parallel mediation model of the relationship between cyberbullying victimization and suicidal ideation. Our study may help to develop interventions and prevention measures for college students who experienced cyberbullying victimization.